12.9k views
0 votes
X-3÷4x^4-8x^3-18x^2+17x+3​

1 Answer

3 votes

Answer:

The simplication of x-3÷4x^4-8x^3-18x^2+17x+3 is
(1)/(\left(4 x^(3)+4 x^(2)-6 x-1\right))

Solution:


\text { Given, expression is }(x-3) /\left(4 x^(4)-8 x^(3)-18 x^(2)+17 x+3\right)

Now we have to simplify the given expression,

For that, we have to factorize the denominator.


\text { So, } 4 x^(4)-8 x^(3)-18 x^(2)+17 x+3


\Rightarrow 4 x^(4)+\left(-12 x^(3)+4 x^(3)\right)+\left(-12 x^(2)-6 x^(2)\right)+(18 x-x)+3

By grouping terms we get,


\rightarrow\left(4 x^(4)-12 x^(3)\right)+\left(4 x^(3)-12 x^(2)\right)-\left(6 x^(2)-18 x\right)-(x-3)

By taking the common terms,


\begin{array}{l}{\rightarrow 4 x^(3)(x-3)+4 x^(2)(x-3)-6 x(x-3)-(x-3)} \\\\ {\rightarrow(x-3)\left(4 x^(3)+4 x^(2)-6 x-1\right)}\end{array}


\begin{array}{l}{\text { Now, }(x-3) /\left(4 x^(4)-8 x^(3)-18 x^(2)+17 x+3\right) \rightarrow (x-3)/(\left(4 x^(4)-8 x^(3)-18 x^(2)+17 x+3\right))} \\\\ {\quad \rightarrow (x-3)/((x-3)\left(4 x^(3)+4 x^(2)-6 x-1\right))} \\\\ {\quad \rightarrow (1)/(\left(4 x^(3)+4 x^(2)-6 x-1\right))}\end{array}

Hence, the simplified expression is
(1)/(\left(4 x^(3)+4 x^(2)-6 x-1\right))

User Pasine
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.